The Effect of Knowledge and Attitudes on Waste Management among the Community in Manggala District, Makassar City - Dewi Yuyun; Muhiddin Palennari; Muhammad Arsyad; Firdaus Daud; Halimah Husain (Jurnal Penelitian Pendidikan IPA, 2026)
This research aims to analyze the effect of understanding and attitude, both partially and simultaneously, on waste management among the community in Manggala District, Makassar City. This study employed a quantitative approach with an ex post facto research design. The research population included all heads of households in Manggala District. Sampling was conducted using a cluster random sampling technique, obtaining a sample of 380 respondents. Data collection was carried out using test instruments to measure understanding, as well as Likert scale questionnaire instruments to measure attitude and waste management. The collected data were analyzed using descriptive and inferential statistics. The results of the descriptive analysis showed that the community's understanding, attitude, and waste management were generally in the moderate category. The results of the inferential analysis indicated a significant effect of understanding on waste management, a positive and significant effect of attitude on waste management, and a significant simultaneous effect of understanding and attitude on waste management.